Some of The Legal Implications Procedure Regulation no. 15 of 2020 Concerning Stopping Prosecution Based on Restorative Justice - Yuli Indarsih (LEGAL BRIEF, 2021)
The Attorney General Regulation Number 15 Year 2020 Regarding the Cessation of Prosecution Based on Restorative Justice (PERJA 15/2020) stipulates that a criminal case can be terminated if it fulfills certain conditions, including the settlement agreement between the victim and offender has been achieved. Principally, this regulation reflects and implements the process or mechanism of the restorative justice principles, whereby such criminal case finally will be settled through the out of court settlement. PERJA 15/2020 has some implications, among other things, to the code of criminal procedure (KUHAP), the public prosecutor's new role and responsibility acting as the facilitator for the victim and offender, as well as, the efficiency in the process and settlement of a criminal case. The current code of criminal procedure does not stipulate any provision relating to the restorative justice. Therefore, the legal ground for the public prosecutor to terminate the criminal case under PERJA 15/2020 can be found by extending the interpretation and meaning of the public prosecutor's right and authority given under KUHAP, that is, for ceasing the prosecution process and terminating a case due to legal interest reason. In this case, the out of court settlement under the restorative justice has been included in the meaning of legal interest. Due to the additional role and responsibility given to the public prosecutor under PERJA 15/2020, it is required to improve of public prosecutor's skill and knowledge as the facilitator with respect to the restorative justice process and implementation. Ideally, PERJA 15/2020 would be useful not only the efficiency of criminal case proceeding, but also the victim and offender. By recognizing the restorative justice, it is urgently required to reform the laws relating to the criminal justice system comprehensively.